Chukchi and Bering Sea surface water particulate organic matter distributions (summer/fall 2012, 2015, 2016, 2017) - Miguel Goni (Arctic Data Center, 2018)
The samples and data presented were collected during four separate cruises aboard three different research vessels, including United States Coast Guard Cutter (USCGC) Healy, National Oceanographic and Atmospheric Administration (NOAA) Research Vessel Ronald H. Brown and University-National Oceanographic Laboratory System (UNOLS) Research Vessel Sikuliaq, operated by University of Alaska-Fairbanks. The USCGC Healy cruise (HLY1203) sailed from Dutch Harbor to Dutch Harbor (AK) from October 5 to 25, 2012. The Ronald H. Brown cruise (RB1505) sailed from Kodiak (AK) to Dutch Harbor (AK) from August 6 to September 4, 2015. The RV Sikuliaq cruise in 2016 included a transit leg (SKQ201611T) from Seward (AK) to Nome (AK) from August 26 to 31, 2016 and a science leg (SKQ201612S) from Nome to Nome from September 3 to 25, 2016. In 2017, the RV Sikuliaq cruise included a transit leg (SKQ201711T) that sailed from Seward to Nome from August 1 to August 5, 2017 and a science leg (SQK201712S) from August 7 to 21, 2017. For the two Sikuliaq cruises, we have combined the data from each transit and science legs and will refer to those data sets as SKQ2016 and SQK2017, respectively. All surface underway data (date and time, latitude, longitude, salinity, temperature, POC and PN concentrations) are presented.